Revisiting Individual Entrepreneurial Orientation Theory: A Study of Indonesian Entrepreneurs - Setyowibowo, Feri (Curtin University, 2019)
Individual Entrepreneurial Orientation (IEO) is a new concept and consensus on its dimensions have not yet been reached. This research aims to validate IEO in the Indonesian context. Data was analysed using Structural Equation Modelling. There are four significant finding, with the most important being IEO, with five dimensions, contributed as a mediating variable for human capital and personality traits toward entrepreneurial performance. This provides a basis for development of IEO in the future.